A RARE CASE OF ADENOCARCINOMA OF THE ILEUM - G. Ts. Dambaev; M. M. Solovyev; S. V. Vtorushin; V. V. Skidanenko; O. A. Fatyushina; Yu. F. Bykova (Сибирский онкологический журнал)
Problems in diagnosis and treatment of small intestine cancer are related to the rarity of the disease as well as to the non-specificity of clinical signs and symptoms. This case report describes difficulties in diagnosis of adenocarcinoma of the ileum